Manganese-based oxide material, preparation method, positive pole piece, battery and electric equipment

By doping lithium, nickel and zirconium elements into manganese-based oxide materials to form materials with P2 phase crystal structure, the problem of insufficient activity and reversibility of the positive electrode material of sodium ion battery is solved, and the discharge specific capacity and cycle stability are significantly improved sex.

CN119481029AActive Publication Date: 2025-02-18SONGSHAN LAKE MATERIALS LAB
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411466443.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-02-18
Estimated Expiration
2044-10-21

AI Technical Summary

Technical Problem

The existing sodium ion battery positive electrode materials have poor activity and reversibility during the redox reaction, resulting in insufficient discharge specific capacity and capacity retention rate.

Method used

Manganese-based oxide material with P2 phase crystal structure characteristics is used. This material significantly improves the activity and reversibility of anionic redox reaction by doping lithium, nickel and zirconium elements, and enhances the stability of the crystal structure.

Benefits of technology

The discharge specific capacity and cycle stability of manganese-based oxide materials are significantly improved, the reversibility of the material in a highly desodiumed state is ensured, and the occurrence of irreversible phase change is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a manganese-based oxide material, a preparation method, a positive pole piece, a battery and electric equipment. The manganese-based oxide material has the characteristic of a P2-phase crystal structure, the chemical formula of the manganese-based oxide material is NamLiaNibZrcM1-a-b-c-dMndO2, M comprises one or more of Al, Ru and Fe, and M does not contain Co; wherein 0 < a < = 0.2, 0 < b < = 0.2, 0.01 < = c < = 0.2, and d > = 0.5. The manganese-based oxide material has remarkably high specific discharge capacity and long cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to a manganese-based oxide material, a preparation method, a positive electrode sheet, a battery and electrical equipment. Background Art

[0002] Lithium-ion batteries are a type of secondary battery system that has been widely used in commercial applications. Lithium-containing materials must be used in lithium-ion batteries. The limited reserves and high cost of lithium resources are important factors that restrict the further development of lithium-ion batteries. Compared with lithium resources, sodium resources have significantly more abundant reserves and are cheaper to obtain, so they have a wider range of application prospects.

[0003] The improvement of the energy density of sodium-ion batteries depends largely on the improvement of the reversible capacity and voltage of the positive electrode materials. Compared with lithium ions, sodium ions are larger in size and have more stringent requirements in terms of material structure stability and kinetic performance. The development of sodium-ion battery positive electrode materials with commercial prospects is more challenging. New layered oxides with mixed cations and oxygen anions have higher operating voltage and higher specific capacity, which has attracted widespread attention. However, the activity and reversibility of this type of oxide material in the redox reaction process are still poor, and the discharge specific capacity and capacity retention rate during the charge and discharge process need to be further improved. Summary of the invention

[0004] Based on this, it is necessary to provide a manganese-based oxide material that can improve the capacity retention rate while obtaining a higher discharge specific capacity in response to the problems in the above-mentioned background technology.

[0005] In a first aspect, according to some embodiments of the present disclosure, a manganese-based oxide material is provided, wherein the manganese-based oxide material has a P2 phase crystal structure characteristic, and the chemical formula of the manganese-based oxide material is Na m Li a Ni b Zr c M 1-a-b-c- d Mn d O2, M includes one or more of Al, Ru and Fe and M does not contain Co; wherein, 0<a≤0.2, 0<b≤0.2, 0.01≤c≤0.2, d≥0.5.

[0006] In some embodiments of the present disclosure, in the manganese-based oxide material, 0.05≤b≤0.15; and / or,

[0007] In the manganese-based oxide material, 0.03≤c≤0.15; and / or,

[0008] In the manganese-based oxide material, d≥0.6; and / or,

[0009] In the manganese-based oxide material, 0≤1-abcd≤0.1.

[0010] In some embodiments of the present disclosure, in the manganese-based oxide material, b:c=1:(0.4-2); and / or,

[0011] In the manganese-based oxide material, b:d=1:(5~8).

[0012] In some embodiments of the present disclosure, 0.6≤m≤0.9.

[0013] In some embodiments of the present disclosure, in the manganese-based oxide material, a:b=(4-10):1.

[0014] In some embodiments of the present disclosure, the chemical formula of the manganese-based oxide material is selected from Na 0.82 Li 0.12 Ni 0.12 Ru 0.05 Zr 0.05 Mn 0.66 O2、Na 0.78 Li 0.10 Ni 0.10 Ru 0.05 Zr 0.05 Mn 0.70 O2、Na 0.75 Li 0.10 Ni 0.10 Al 0.04 Zr 0.06 Mn 0.70 O2、Na 0.80 Li 0.10 Ni 0.10 Fe 0.05 Zr 0.05 Mn 0.70 O2 or Na 0.80 Li 0.10 Ni 0.08 Zr 0.12 Mn 0.70 O2.

[0015] In a second aspect, according to some embodiments of the present disclosure, a method for preparing a manganese-based oxide material is also provided, comprising the following steps:

[0016] A sodium source, a lithium source, a nickel source, a zirconium source, a manganese source and an M source are mixed in a ratio of m:a:b:c:d:(1-abcd) and ball-milled to form a mixed precursor;

[0017] The mixed precursor is calcined, and the calcination temperature is controlled to be 700° C. to 950° C.

[0018] In a third aspect, according to some embodiments of the present disclosure, a positive electrode plate is also provided, which includes a current collector and an active material layer disposed on the current collector, and the active material layer includes the manganese-based oxide material as described in any of the above embodiments.

[0019] In a third aspect, according to some embodiments of the present disclosure, a battery is also provided, which includes a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode and the negative electrode are arranged opposite to each other, the electrolyte is located between the positive electrode and the negative electrode, and the positive electrode includes the manganese-based oxide material as described in any of the above embodiments, or the positive electrode includes the positive electrode plate as described in any of the above embodiments.

[0020] In a fourth aspect, according to some embodiments of the present disclosure, there is also provided an electrical device, which includes a functional body and a battery as described in any of the above embodiments, wherein the battery is used to supply energy to the functional body.

[0021] The chemical formula of the manganese-based oxide material in at least one embodiment of the present disclosure is Na m Li a Ni b Zr c M 1-a-b-c- d Mn d O2 and has the characteristics of P2 phase crystal structure, which is a layered manganese-based oxide material. Among them, lithium, nickel and zirconium are used to replace part of the manganese element. The inventors of the present disclosure found in the research process that the use of lithium, nickel and zirconium elements in the above proportions to dope into manganese-based oxide materials can significantly improve the activity and reversibility of anion redox reactions, enhance the stability of the crystal structure, and inhibit the irreversible phase change of the material under a highly de-sodiumized state. Therefore, the manganese-based oxide material has a significantly higher discharge specific capacity and long cycle stability. In addition, the manganese-based oxide material of at least one embodiment of the present disclosure does not contain elements such as cobalt, and also has the advantages of abundant raw materials, low cost, and non-toxicity.

[0022] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a description of the preferred embodiments of the present invention. DETAILED DESCRIPTION

[0023] The following is a detailed description of the embodiments of the technical solution of the present application. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the description and claims of this application and any variations thereof are intended to cover non-exclusive inclusions.

[0025] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0026] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0027] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0028] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).

[0029] In the description of the embodiments of the present application, unless otherwise clearly specified and limited, technical terms such as "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, and it can be the internal connection of two elements or the interaction relationship between two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the embodiments of the present application can be understood according to the specific circumstances.

[0030] In a first aspect, an embodiment of the present disclosure provides a manganese-based oxide material, the manganese-based oxide material has a P2 phase crystal structure characteristic, and the chemical formula of the manganese-based oxide material is Na m Lia Ni b Zr c M 1-a-b-c-d Mn d O2, M includes one or more of Al, Ru and Fe and M does not contain Co; wherein, 0<a≤0.2, 0<b≤0.2, 0.01≤c≤0.2, d≥0.5, 0≤1-abcd≤0.1.

[0031] The chemical formula of the manganese-based oxide material in this embodiment is Na m Li a Ni b Zr c M 1-a-b-c-d Mn d O2 and has the characteristics of P2 phase crystal structure, which is a layered manganese-based oxide material. Among them, lithium, nickel and zirconium are used to replace part of the manganese element. The inventors of the present disclosure found in the research process that the use of lithium, nickel and zirconium elements in the above proportions to dope into manganese-based oxide materials can significantly improve the activity and reversibility of anion redox reactions, enhance the stability of the crystal structure, and inhibit the irreversible phase change of the material under a highly de-sodiumized state. Therefore, the manganese-based oxide material has a significantly higher discharge specific capacity and long cycle stability. In addition, the manganese-based oxide material of at least one embodiment of the present disclosure does not contain elements such as cobalt, and also has the advantages of abundant raw materials, low cost, and non-toxicity.

[0032] It can be understood that in this embodiment, the Li element, the Ni element, the Zr element and the M element are used together as doping elements to replace the Mn element in the crystal lattice, while also allowing the manganese-based oxide material to maintain the P2 phase crystal structure characteristics. The P2 phase crystal structure characteristics can be determined by the diffraction peak position in the XRD diffraction image.

[0033] As an example of this embodiment, in the manganese-based oxide material, 0.05≤b≤0.15. In some examples, in the manganese-based oxide material, the value of b can be 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, or the value of b can be between any two of the above values. The value of b within this range can effectively suppress the irreversible phase change of the material in a highly de-sodiumized state, thereby obtaining higher cycle stability.

[0034] As an example of this embodiment, in the manganese-based oxide material, 0.03≤c≤0.15. In some examples, in the manganese-based oxide material, the value of c can be 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, or the value of c can be between any two of the above values. The value of c within this range can effectively suppress the irreversible phase change of the material in a highly de-sodiumized state, thereby obtaining higher cycle stability.

[0035] As an example of this embodiment, in the manganese-based oxide material, b:c=1:(0.4~2). In some examples, the ratio of b to c is 1:0.4, 1:0.5, 1:0.6, 1:0.8, 1:1, 1:1.2, 1:1.4, 1:1.6, 1:1.8, 1:2, or the ratio of b to c can also be between any two of the above ratios. The Ni element and the Zr element are between this ratio, which is conducive to the Ni element and the Zr element to play a better synergistic role, thereby effectively improving the charge and discharge specific capacity and cycle stability of the material.

[0036] As an example of this embodiment, in a manganese-based oxide material, d≥0.6. As a further example of this embodiment, d≤0.8. In some examples, the value of d can be 0.6, 0.62, 0.64, 0.66, 0.68, 0.7, 0.72, 0.74, 0.76, 0.78, 0.8, or the value of d can also be between any two of the above values.

[0037] As an example of this embodiment, in the manganese-based oxide material, b:d=1:(5~8). In some examples, the ratio of b to d is 1:5, 1:5.5, 1:6, 1:6.5, 1:7, 1:7.5, 1:8, or the ratio of b to d can also be between any two of the above ratios. The ratio of Ni element to Mn element is conducive to obtaining a higher charge-discharge specific capacity and capacity retention rate while ensuring a relatively stable overall lattice structure.

[0038] As an example of this embodiment, 0.6≤m≤0.9. In some examples, m may be 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, or the value of m may be between any two of the above values.

[0039] As an example of this embodiment, in the manganese-based oxide material, a:b=(4-10): 1. In some examples, the ratio of a to b can be 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, or the ratio of a to b can be between any two of the above ratios.

[0040] As an example of this embodiment, the chemical formula of the manganese-based oxide material is selected from Na 0.82 Li 0.12 Ni 0.12 Ru 0.05 Zr 0.05 Mn 0.66 O2、Na 0.78 Li 0.10 Ni 0.10 Ru 0.05 Zr 0.05 Mn 0.70 O2、Na 0.75 Li 0.10 Ni 0.10 Al 0.04 Zr 0.06 Mn 0.70 O2、Na 0.80 Li 0.10 Ni 0.10 Fe 0.05 Zr 0.05 Mn 0.70 O2 or Na 0.80 Li 0.10 Ni 0.08 Zr 0.12 Mn 0.70 The manganese-based oxide material having the chemical formula can exhibit significantly higher initial discharge specific capacity and more stable cycle performance.

[0041] In a second aspect, the present disclosure further provides a method for preparing a manganese-based oxide material as described in any of the above embodiments, comprising the following steps S1 to S2.

[0042] Step S1, mixing a sodium source, a lithium source, a nickel source, a zirconium source, a manganese source and an M source and subjecting them to ball milling to form a mixed precursor.

[0043] It can be understood that the amount of the sodium source, lithium source, nickel source, zirconium source, manganese source and M source corresponds to the stoichiometric ratio of each element in the manganese-based oxide material finally formed. Therefore, in this embodiment, the sodium source, lithium source, nickel source, zirconium source, manganese source and M source should be mixed in a ratio of m:a:b:c:d:(1-abcd) to obtain a chemical formula of Na m Li a Ni b Zr c M 1-a-b-c-d Mn d O2 manganese-based oxide materials.

[0044] It can be understood that the sodium source contains the Na element, and the sodium source can be a compound containing the Na element. The lithium source contains the Li element, and the lithium source can be a compound containing the Li element. The nickel source contains the Ni element, and the nickel source can be a compound containing the Ni element. The zirconium source contains the nickel element, and the zirconium source can be a compound containing the Zr element. The M source contains the M element, and the M source can be a compound containing the M element. The manganese source contains the manganese element, and the manganese source can be a compound containing the Mn element.

[0045] As an example of this embodiment, the sodium source is selected from one or more of sodium hydroxide, sodium carbonate and sodium oxide. Using sodium hydroxide, sodium carbonate and sodium oxide as the sodium source can ensure that substantially no impurity elements are introduced during the calcination process, which is conducive to the formation of a pure phase manganese-based oxide material.

[0046] As an example of this embodiment, the lithium source is selected from one or more of lithium hydroxide, lithium carbonate and lithium oxide. Using lithium hydroxide, lithium carbonate and lithium oxide as the lithium source can ensure that substantially no impurity elements are introduced during the calcination process, which is conducive to forming a pure phase manganese-based oxide material.

[0047] As an example of this embodiment, the nickel source is selected from one or more of nickel oxide and nickel tert-oxide. Using nickel oxide and nickel tert-oxide as the nickel source can ensure that substantially no impurity elements are introduced during the calcination process, which is conducive to forming a pure phase manganese-based oxide material.

[0048] As an example of this embodiment, the zirconium source is selected from zirconium oxide. Using zirconium oxide as the zirconium source can ensure that substantially no impurity elements are introduced during the calcination process, which is conducive to forming a pure phase manganese-based oxide material.

[0049] It is understood that the M source can be selected according to the required M element. As an example of this embodiment, the M source can be selected from one or more of aluminum oxide, ruthenium oxide and iron oxide. Using aluminum oxide, ruthenium oxide and iron oxide as the M source can ensure that no impurity elements are basically introduced during the calcination process, which is conducive to the formation of a pure phase manganese-based oxide material.

[0050] As an example of this embodiment, during the ball milling process, liquid ball milling media can be added to the ball milling tank to wet-mill the raw materials. The ball milling media can include ethanol.

[0051] As an example of this embodiment, during the ball milling process, the speed of the ball mill may be 200 r / min to 600 r / min. For example, the speed of the ball mill may be 200 r / min, 300 r / min, 400 r / min, 500 r / min, 600 r / min, or the speed of the ball mill may be between any two of the above speeds.

[0052] As an example of this embodiment, during the ball milling process, the ball milling time may be 2 hours to 12 hours. For example, the ball milling time may be 2 hours, 4 hours, 6 hours, 8 hours, 10 hours, or 12 hours, or the ball milling time may be between any two of the above time periods.

[0053] Step S2, calcining the mixed precursor.

[0054] As an example of this embodiment, before the calcination process, the mixed raw materials may be subjected to a tableting process. During the tableting process, the pressure applied to the mixed raw materials may be 2MPa to 10MPa. For example, the pressure applied to the mixed raw materials may be 2MPa, 3MPa, 4MPa, 5MPa, 6MPa, 7MPa, 8MPa, 9MPa, or 10MPa, or the pressure applied to the mixed raw materials may be between any two of the above pressures.

[0055] As an example of this embodiment, during the calcination process, the calcination temperature can be controlled to be 700° C. to 950° C. For example, the calcination temperature can be controlled to be 750° C., 780° C., 800° C., 820° C., 850° C., 880° C., 900° C., 920° C., 950° C., or the calcination temperature can be controlled to be between any two of the above temperatures.

[0056] As some examples of this embodiment, during the calcination process, the calcination time is controlled to be 10 hours to 20 hours. For example, the calcination time can be controlled to be 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, or the calcination time can be controlled to be between any two of the above times.

[0057] The above calcination temperature and calcination time can ensure that the raw materials are combined as fully as possible and converted into the desired manganese-based oxide material.

[0058] It can be understood that through the above steps S1 to S2, the manganese-based oxide material as in the embodiment of the present disclosure can be prepared.

[0059] In a third aspect, the present disclosure further provides a positive electrode plate, which includes a current collector and an active material layer disposed on the current collector, wherein the active material layer includes the manganese-based oxide material as described in the above embodiment.

[0060] It is understood that the manganese-based oxide material can be used as an active material in the positive electrode active layer. The positive electrode active layer can also include other auxiliary materials.

[0061] As a further example of this embodiment, the positive electrode active layer may further include at least one of a conductive agent and a binder. Further, the conductive agent may include one or more of conductive carbon black, acetylene black, carbon fiber, carbon nanotubes and graphene. The binder may include polyvinylidene fluoride.

[0062] The positive electrode active layer of this embodiment can be used as a positive electrode material for a sodium ion battery.

[0063] In a fourth aspect, the present disclosure also provides a battery, which includes a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode and the negative electrode are arranged opposite to each other and spaced apart, the electrolyte is arranged between the positive electrode and the negative electrode, and the positive electrode includes the manganese-based oxide material as in any of the above embodiments, or the positive electrode includes the positive electrode plate as in any of the above embodiments.

[0064] It is understood that the battery may be a sodium ion battery. In the battery, the electrolyte may be a solid electrolyte or a liquid electrolyte. When the electrolyte is a liquid electrolyte, the battery may further include a separator.

[0065] In a fifth aspect, the present disclosure further provides an electrical device, which includes a functional body and a battery as described in the above embodiment, and the battery is used to supply energy to the functional body.

[0066] As an example of this embodiment, the electric device may be selected from, but not limited to, a portable communication device and an electric vehicle.

[0067] The present application is further described in detail below in conjunction with several specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0068] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0069] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.

[0070] Example 1

[0071] According to the molar ratio of Na:Li:Ni:Ru:Zr:Mn=0.82:0.12:0.12:0.05:0.05:0.66, Na2CO3, Li2CO3, NiO, RuO2, ZrO2 and MnO2 were weighed and mixed evenly. Ethanol was used as the ball milling medium, and the mixture was placed in a ball mill. After ball milling at a speed of 400 r / min for 6 hours, it was taken out to obtain a mixed precursor.

[0072] The mixed precursor was pressed into a disc with a diameter of 10 mm under a pressure of 8 MPa, heated to 850°C in a muffle furnace and calcined for 15 hours. It was then naturally cooled to room temperature, taken out and ground into powder to obtain a manganese-based oxide material, the chemical formula of which is Na 0.82 Li 0.12 Ni 0.12 Ru 0.05 Zr 0.05 Mn 0.66 O2.

[0073] Example 2

[0074] According to the molar ratio of Na:Li:Ni:Ru:Zr:Mn=0.78:0.1:0.1:0.05:0.05:0.7, Na2CO3, Li2CO3, NiO, RuO2, ZrO2 and MnO2 were weighed and mixed evenly. Ethanol was used as the ball milling medium, and the mixture was placed in a ball mill. After ball milling at a speed of 400 r / min for 6 hours, it was taken out to obtain a mixed precursor.

[0075] The mixed precursor was pressed into a disc with a diameter of 10 mm under a pressure of 8 MPa, heated to 850°C in a muffle furnace and calcined for 15 hours. It was then naturally cooled to room temperature, taken out and ground into powder to obtain a manganese-based oxide material, the chemical formula of which is Na 0.78 Li 0.10 Ni 0.10 Ru 0.05 Zr 0.05 Mn 0.70 O2.

[0076] Example 3

[0077] According to the molar ratio of Na:Li:Ni:Al:Zr:Mn=0.75:0.1:0.1:0.04:0.06:0.7, Na2CO3, Li2CO3, NiO, Al2O3, ZrO2 and MnO2 were weighed and mixed evenly. Ethanol was used as the ball milling medium, and the mixture was placed in a ball mill. After ball milling at a speed of 400 r / min for 6 hours, it was taken out to obtain a mixed precursor.

[0078] The mixed precursor was pressed into a disc with a diameter of 10 mm under a pressure of 8 MPa, heated to 850°C in a muffle furnace and calcined for 15 hours. It was then naturally cooled to room temperature, taken out and ground into powder to obtain a manganese-based oxide material, the chemical formula of which is Na 0.75 Li 0.10 Ni 0.10 Al 0.04 Zr 0.06 Mn 0.70 O2.

[0079] Example 4

[0080] According to the molar ratio of Na:Li:Ni:Fe:Zr:Mn=0.8:0.1:0.1:0.05:0.05:0.7, Na2CO3, Li2CO3, NiO, Fe2O3, ZrO2 and MnO2 were weighed and mixed evenly. Ethanol was used as the ball milling medium, and the mixture was placed in a ball mill. After ball milling at a speed of 400 r / min for 6 hours, it was taken out to obtain a mixed precursor.

[0081] The mixed precursor was pressed into a disc with a diameter of 10 mm under a pressure of 8 MPa, heated to 850°C in a muffle furnace and calcined for 15 hours. It was then naturally cooled to room temperature, taken out and ground into powder to obtain a manganese-based oxide material, the chemical formula of which is Na 0.80 Li 0.10 Ni 0.10 Fe 0.05 Zr 0.05 Mn 0.70 O2.

[0082] Example 5

[0083] According to the molar ratio of Na:Li:Ni:Zr:Mn=0.8:0.1:0.08:0.12:0.7, Na2CO3, Li2CO3, NiO, ZrO2 and MnO2 were weighed and mixed evenly. Ethanol was used as the ball milling medium, and the mixture was placed in a ball mill. After ball milling at a speed of 400 r / min for 6 hours, it was taken out to obtain a mixed precursor.

[0084] The mixed precursor was pressed into a disc with a diameter of 10 mm under a pressure of 8 MPa, heated to 850°C in a muffle furnace and calcined for 15 hours. It was then naturally cooled to room temperature, taken out and ground into powder to obtain a manganese-based oxide material, the chemical formula of which is Na 0.80 Li 0.10 Ni 0.08 Zr 0.12 Mn 0.70 O2.

[0085] Comparative Example 1

[0086] According to the molar ratio of Na:Li:Ru:Zr:Mn=0.82:0.12:0.05:0.05:0.78, Na2CO3, Li2CO3, RuO2, ZrO2 and MnO2 were weighed and mixed evenly. Ethanol was used as the ball milling medium, and the mixture was placed in a ball mill. After ball milling at a speed of 400 r / min for 6 hours, it was taken out to obtain a mixed precursor.

[0087] The mixed precursor was pressed into a disc with a diameter of 10 mm under a pressure of 8 MPa, heated to 850°C in a muffle furnace and calcined for 15 hours. It was then naturally cooled to room temperature, taken out and ground into powder to obtain a manganese-based oxide material, the chemical formula of which is Na 0.82 Li 0.12 Ru 0.05 Zr 0.05 Mn 0.78 O2.

[0088] Comparative Example 2

[0089] According to the molar ratio of Na:Li:Ni:Ru:Mn=0.82:0.12:0.12:0.05:0.71, Na2CO3, Li2CO3, NiO, RuO2 and MnO2 were weighed and mixed evenly. Ethanol was used as the ball milling medium, and the mixture was placed in a ball mill. After ball milling at a speed of 400r / min for 6h, it was taken out to obtain a mixed precursor.

[0090] The mixed precursor was pressed into a disc with a diameter of 10 mm under a pressure of 8 MPa, heated to 850°C in a muffle furnace and calcined for 15 hours. It was then naturally cooled to room temperature, taken out and ground into powder to obtain a manganese-based oxide material, the chemical formula of which is Na 0.82 Li 0.12 Ni 0.12 Ru 0.05 Mn 0.71 O2.

[0091] Comparative Example 3

[0092] According to the molar ratio of Na:Ni:Ru:Zr:Mn=0.82:0.12:0.05:0.05:0.78, Na2CO3, NiO, RuO2, ZrO2 and MnO2 were weighed and mixed evenly. Ethanol was used as the ball milling medium, and the mixture was placed in a ball mill. After ball milling at a speed of 400 r / min for 6 hours, it was taken out to obtain a mixed precursor.

[0093] The mixed precursor was pressed into a disc with a diameter of 10 mm under a pressure of 8 MPa, heated to 850°C in a muffle furnace and calcined for 15 hours. It was then naturally cooled to room temperature, taken out and ground into powder to obtain a manganese-based oxide material, the chemical formula of which is Na 0.82 Ni 0.12 Ru 0.05 Zr 0.05 Mn 0.66 O2.

[0094] Comparative Example 4

[0095] According to the molar ratio of Na:Li:Ni:Ru:Zr:Mn=0.82:0.12:0.3:0.05:0.05:0.48, Na2CO3, Li2CO3, NiO, RuO2, ZrO2 and MnO2 were weighed and mixed evenly. Ethanol was used as the ball milling medium, and the mixture was placed in a ball mill. After ball milling at a speed of 400 r / min for 6 hours, it was taken out to obtain a mixed precursor.

[0096] The mixed precursor was pressed into a disc with a diameter of 10 mm under a pressure of 8 MPa, heated to 850°C in a muffle furnace and calcined for 15 hours. It was then naturally cooled to room temperature, taken out and ground into powder to obtain a manganese-based oxide material, the chemical formula of which is Na 0.82 Li 0.12 Ni 0.3 Ru 0.05 Zr 0.05 Mn 0.48 O2.

[0097] Comparative Example 5

[0098] According to the molar ratio of Na:Li:Ni:Ru:Zr:Mn=0.82:0.12:0.12:0.05:0.25:0.46, Na2CO3, Li2CO3, NiO, RuO2, ZrO2 and MnO2 were weighed and mixed evenly. Ethanol was used as the ball milling medium, and the mixture was placed in a ball mill. After ball milling at a speed of 400 r / min for 6 hours, it was taken out to obtain a mixed precursor.

[0099] The mixed precursor was pressed into a disc with a diameter of 10 mm under a pressure of 8 MPa, heated to 850°C in a muffle furnace and calcined for 15 hours. It was then naturally cooled to room temperature, taken out and ground into powder to obtain a manganese-based oxide material, the chemical formula of which is Na 0.82 Li 0.12 Ni 0.12 Ru 0.05 Zr 0.25 Mn 0.46 O2.

[0100] Comparative Example 6

[0101] According to the molar ratio of Na:Li:Ni:Ru:Zr:Mn=0.82:0.12:0.12:0.05:0.005:0.705, Na2CO3, Li2CO3, NiO, RuO2, ZrO2 and MnO2 were weighed and mixed evenly. Ethanol was used as the ball milling medium, and the mixture was placed in a ball mill. After ball milling at a speed of 400 r / min for 6 hours, it was taken out to obtain a mixed precursor.

[0102] The mixed precursor was pressed into a disc with a diameter of 10 mm under a pressure of 8 MPa, heated to 850°C in a muffle furnace and calcined for 15 hours. It was then naturally cooled to room temperature, taken out and ground into powder to obtain a manganese-based oxide material, the chemical formula of which is Na 0.82 Li 0.12 Ni 0.12 Ru 0.05 Zr 0.005 Mn 0.705 O2.

[0103] Preparation of positive electrode sheet: The manganese-based oxide material, conductive agent SuperP and binder PVDF prepared in the above embodiments and comparative examples were mixed and ground evenly in a mass ratio of 80:10:10, added to nitrogen methyl pyrrolidone (NMP) and ground again to form a slurry. The slurry was evenly coated on the aluminum foil current collector, and then dried in a vacuum oven at 120°C for 12 hours to form a positive electrode sheet.

[0104] Assembly and testing of sodium ion batteries: Sodium metal is used as the negative electrode and glass fiber membrane is used as the diaphragm. The negative electrode, diaphragm and the positive electrode plate are stacked in a CR2032 battery shell and filled with electrolyte. The solvent of the electrolyte is a mixed solvent of propylene carbonate and ethylene carbonate, and the solute of the electrolyte is 1 mol / L NaClO4. After the assembly is completed, the charge and discharge test is carried out in the voltage range of 1.5V~4.5V. First, the first cycle of charge and discharge is carried out at a current density of 20mA / g, and its initial discharge specific capacity is recorded. Then, 50 charge and discharge cycles are carried out at a current density of 100mA / g, and its capacity retention rate is recorded. The results can be seen in Table 1.

[0105] Table 1

[0106]

[0107] Referring to the contents shown in Table 1, compared with Comparative Examples 1 to 6, the sodium ion battery prepared in Example 1 achieved significantly higher initial discharge specific capacity and capacity retention rate. Among them, compared with Example 1, the manganese-based oxide material of Comparative Example 1 does not contain Ni element, the manganese-based oxide material of Comparative Example 2 does not contain Zr element, and the manganese-based oxide material of Comparative Example 3 does not contain Li element. Comparative Examples 1 to 3 illustrate that the doping of Ni element, Zr element and Li element plays an important role in improving the initial discharge specific capacity and capacity retention rate. The content of Ni element in the manganese-based oxide material of Comparative Example 4 reaches 0.3, the content of Zr element in the manganese-based oxide material of Comparative Example 5 reaches 0.25, and the content of Zr in the manganese-based oxide material of Comparative Example 6 is only 0.005. Comparative Examples 4 to 6 illustrate that excessive doping of Ni element, excessive doping of Zr element or how much will lead to a decrease in initial discharge specific capacity and capacity retention rate.

[0108] Furthermore, compared with Example 1, the initial discharge specific capacity and / or capacity retention rate of Examples 2 to 5 are slightly different, which is mainly due to the difference in doping elements or doping contents. But overall, Examples 1 to 5 can achieve a capacity retention rate of more than 91% on the basis of obtaining an initial discharge specific capacity of 190 mAh / g. This is mainly because the appropriate amount of doping with Li, Ni, and Zr elements can significantly improve the activity and reversibility of anion redox reactions, enhance the stability of the crystal structure, and inhibit the irreversible phase change of the material under a highly de-sodiumized state. In general, the doping amount of Ni element is controlled below 0.2, and the doping amount of Zr element is controlled between 0.01 and 0.2, which can effectively improve the capacity retention rate while obtaining a higher initial discharge specific capacity.

[0109] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A manganese-based oxide material, characterized in that: The manganese-based oxide material has a P2 phase crystal structure characteristic, and the chemical formula of the manganese-based oxide material is Na m Li a Ni b Zr c M 1-a-b-c-d Mn d O2, M includes one or more of Al, Ru and Fe and M does not contain Co; wherein, 0<a≤0.2, 0<b≤0.2, 0.01≤c≤0.2, d≥0.

5.

2. The manganese-based oxide material according to claim 1, characterized in that In the manganese-based oxide material, 0.05≤b≤0.15; and / or, In the manganese-based oxide material, 0.03≤c≤0.15; and / or, In the manganese-based oxide material, d≥0.6; and / or, In the manganese-based oxide material, 0≤1-abcd≤0.

1.

3. The manganese-based oxide material according to claim 2, characterized in that: In the manganese-based oxide material, b:c=1:(0.4-2); and / or, In the manganese-based oxide material, b:d=1:(5~8).

4. The manganese-based oxide material according to any one of claims 1 to 3, characterized in that 0.6≤m≤0.9。 5. The manganese-based oxide material according to claim 4, characterized in that: In the manganese-based oxide material, a:b=(4~10):

1.

6. The manganese-based oxide material according to any one of claims 1 to 3 and 5, characterized in that: The chemical formula of the manganese-based oxide material is selected from Na 0.82 Li 0.12 Ni 0.12 Ru 0.05 Zr 0.05 Mn 0.66 O2、Na 0.78 Li 0.10 Ni 0.10 Ru 0.05 Zr 0.05 Mn 0.7 0O2、Na 0.75 Li 0.10 Ni 0.10 Al 0.04 Zr 0.06 Mn 0.70 O2、Na 0.80 Li 0.10 Ni 0.10 Fe 0.05 Zr 0.05 Mn 0.70 O2 or Na 0.80 Li 0.1 0Ni 0.08 Zr 0.12 Mn 0.70 O2.

7. A method for preparing the manganese-based oxide material according to any one of claims 1 to 6, characterized in that: The steps include: A sodium source, a lithium source, a nickel source, a zirconium source, a manganese source and an M source are mixed in a ratio of m:a:b:c:d:(1-abcd) and ball-milled to form a mixed precursor; The mixed precursor is calcined, and the calcination temperature is controlled to be 700° C. to 950° C.

8. A positive electrode sheet, characterized in that: It comprises a current collector and an active material layer disposed on the current collector, wherein the active material layer comprises the manganese-based oxide material according to any one of claims 1 to 6.

9. A battery, characterized in that: It comprises a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode and the negative electrode are arranged opposite to each other, the electrolyte is located between the positive electrode and the negative electrode, the positive electrode comprises the manganese-based oxide material as described in any one of claims 1 to 6, or the positive electrode comprises the positive electrode plate as described in claim 8.

10. An electrical device, characterized in that: It comprises a functional body and a battery as claimed in claim 9, wherein the battery is used to supply energy to the functional body.

Citation Information

Patent Citations

  • Preparation method of high-entropy oxide sodium ion battery positive electrode material

    CN115207341A

  • Layered sodium ion medium-high entropy composite oxide positive electrode material

    CN115863625A

  • P-phase-like layered sodium transition metal oxide positive electrode material, preparation method and battery

    CN117577824A

  • Manganese-based layered oxide material, positive electrode material, sodium-ion battery and electric device

    CN118062901A

  • Positive electrode active material, method for producing same, and non-aqueous electrolyte secondary battery

    CN118715633A